Leitura literária : um estudo de propostas de leitura de poesia em livros didáticos - Gonçalves, Maria de Lourdes Bacicheti (2009)
Since the school's task in the formation of the literary text's reader is highly important, current research consists of a descriptive study of poetry reading in two textbook series. They were the most adopted collections by government public schools in Maringá PR Brazil for students of the 3rd and 4th grades of the Primary School, during 2008. Our aim is to know and understand the foregrounding of the reading of the poetic text in the series and to analyze whether they contribute towards the formation of the literary reader. Current analysis has been undertaken since the school has an important role in reader formation. In fact, it contributes towards proper schooling and provides students with the conditions and practice that would lead them towards autonomy in reading. Investigations on literary reading, a practice built and based on models provided by theory of literature, form the bases on which the theoretical orientation for analysis of the studied corpus are foregrounded. Reading codes and conventions of the several genres in which literature may manifest itself should be known so that literary reading may be achieved. Analysis of the research corpus has been undertaken through a qualitative approach and aims at verifying the manner book series are structured and organized; the number of literary texts and of poetic texts; the manner poetry reading suggestions are given and the entire insertion process of the teaching of poetry. Results show that textbooks have a serious concern on the aesthetic quality of literary texts and reveal what other research work has already shown, or rather, that literature, poetry in particular, is losing ground in the school environment. In fact, it is a genre with slight relevance in the textbook, verified by the quality and small number of reading suggestions. Reading approaches do not help the reader to analyze how codes contribute towards the poetic construction, how the different levels of poem composition interfere in the meaning, influence their effects, and compete towards the creation of ideas and the establishment of emotions. Poetry texts are still linked to suggestion in text production, to the study of linguistic aspects, to contents reinforcement and others. No systematic and continuous research exists for the progressive understanding of specificities of the genre and on an all-embracing and reflexive knowledge of the structural elements which constitute poetry and, consequently, relevant to reading. Suggestions for poetry reading in textbooks should be revised, broadened and systemized to understand its specific nature as a genre. Thus, it may contribute towards readers' formation of the literary genre. Current investigation is an attempt towards deeper reflections on the reading of the literary text, especially poetry and for the improvement in the process of literary readers' formation within the school milieu.